2020
DOI: 10.1093/ckj/sfz178
|View full text |Cite
|
Sign up to set email alerts
|

Direct-acting antiviral therapy improves kidney survival in hepatitis C virus-associated cryoglobulinaemia: the RENALCRYOGLOBULINEMIC study

Abstract: Background Direct-acting antiviral agents (DAAs) have shown high rates of sustained virological response in chronic hepatitis C virus (HCV) infection. However, the influence of DAAs on the course of kidney involvement in HCV-associated mixed cryoglobulinaemia (HCV-MC) has been little studied. The aim of this study was to analyse the effects of antiviral treatment on kidney prognosis and evolution in patients diagnosed with HCV-MC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…While Sise et al (22) found no change in kidney function during treatment course as patients experienced minor fluctuations in serum creatinine and did not change >0.3 mg/dL from baseline at any time during treatment. Other studies agree with our results and describe improvement in eGFR after viral clearance (18,20,23) .…”
Section: Discussionsupporting
confidence: 93%
“…While Sise et al (22) found no change in kidney function during treatment course as patients experienced minor fluctuations in serum creatinine and did not change >0.3 mg/dL from baseline at any time during treatment. Other studies agree with our results and describe improvement in eGFR after viral clearance (18,20,23) .…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were detected by Reddy et al, [14] who documented that there is statistical significant difference regarding creatinine as treated patients with HCC group creatinine was lower than untreated patients with HCC group (P < 001). Also Ana et al, [15] documented that DAA treatment in patients with HCV improves kidney survival and reduces creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…In these secondary cases, treatment of the underlying condition—immunosuppression for autoimmune diseases, antiviral drugs and antibiotics for viral and bacterial infections—often also improves kidney injury and dysfunction (Fig. 2 ) [ 2 , 10 , 11 ].…”
Section: Treatment Standardsmentioning
confidence: 99%